Design to enhance sensing performance of ZIF-8 crystals - Li, Ya-Ru; Dong, Xiuxiu; Pan, Shu-Yi; Luo, Lin; Lei, Hong-Tao; Xu, Zhen-Lin (Progress in natural science, 2024)
Metal-organic frameworks (MOFs) are a large class of crystalline porous materials that composed of organic ligands and metal ions, of which zeolitic imidazolate frameworks (ZIFs) are a broad classification. The most well-known ZIF-like material is ZIF-8 crystals, which have been the subject of extensive research for decades. ZIF-8 crystals have been synthesized under various conditions for application in the fields of sensing, drug delivery, and catalysis. This paper provides a brief introduction to the preparation methods, formation processes, and formation mechanisms of ZIF-8 crystals in different media, and then explains the effects of different precursor conditions (type of Zn2+, ratio of raw materials, and type of solvent) on ZIF-8 crystals in terms of formation mechanisms. Subsequently, current reports on the application of ZIF-8-based chemiresistive gas sensors, electrochemical, fluorescent and colorimetric sensors are also summarized. Hopefully, ZIF-8 crystals with good catalytic properties will be obtained based on rational design for promoting the application in different fields of the sensors.